2006
DOI: 10.1007/s11661-006-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of lotus-type porous carbon steel by the continuous zone melting method and its mechanical properties

Abstract: A lotus-type porous carbon steel with cylindrical pores was fabricated by the continuous zone melting method in a pressurized mixture of hydrogen and helium gases. The porosity increases with increasing partial pressure of the hydrogen gas, while the pore diameter remains almost constant, independent of the pressure. The ultimate tensile strength of the specimen with cylindrical pores parallel to the tensile direction is lower than the estimated value, assuming that the strength is decreased in proportion to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The gas blowing method they employed differed from the conventional techniques of porosity formation. It can thus be concluded that the porosity of the lotus-type steel foam increases with increasing partial pressure of hydrogen gas [16].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The gas blowing method they employed differed from the conventional techniques of porosity formation. It can thus be concluded that the porosity of the lotus-type steel foam increases with increasing partial pressure of hydrogen gas [16].…”
Section: Discussionmentioning
confidence: 94%
“…Internal porosity can be developed in a number of ways. Kujime et al [16], for example, applied the gas entrapment method, which involved supplying pressurized hydrogen and helium to a melted metal to produce porous carbon steel with a porosity of 26 % to 44 % and a pore diameter of 500 µm to 700 µm. Compared with the materials described in this article, their lotus-type foams had a structure with larger pores and lower porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kujime et al [5] and Kashihara et al [6,7] produced lotus carbon steel by unidirectional solidification using a continuous zone melting technique. [8] It was reported that the yield strength of the lotus carbon steels fabricated in a nitrogen atmosphere is similar to that of the nonporous carbon steel in the porosity range up to 30 pct, which is attributed to the solid-solution hardening as a result of nitrogen in the steel.…”
Section: Introductionmentioning
confidence: 99%
“…Although this technique is a simple process, it is difficult to control the solidification velocity, which consequently prevents a uniform pore size and porosity for metals with a lower thermal conductivity [12] . In order to improve this shortcoming, we have developed a continuous zone melting technique [13][14][15] and a continuous casting technique. [16][17][18] Because these techniques can control the solidification velocity, various types of lotus metals with homogeneously distributed long pores can be fabricated.…”
Section: Introductionmentioning
confidence: 99%